Desarrollo de una aplicación móvil para la guía interactiva en el Campus Sur de la UPS y la presentación de noticias de la Carrera de Ingeniería de Sistemas usando realidad aumentada, codificación QR y conexión web service - Balseca Rodríguez, Carlos Alejandro (2016)
In this paper the research is about the analysis and design of a prototype for a mobile solution with Augmented Reality, coding QR codes and newsreader's for the degree of Systems to contribute with a technological tool that benefits the user mobility within South of the Salesian Polytechnic University campus providing support to the deployed signage for institution in order to optimize user's time in the campus and also provide a communication tool for dissemination of news for students and teachers for the Carrer of Systems. This project consists of 2 parts. First, the web application developed in C # allowing the entry of information by an administrator user, this information is stored in SQL Server and distributed through web services. Second, the mobile application developed in Java programming language that allows the visualization of information using the resources of the mobile device as camera, QR code reader, accelerometer, gyroscope, etc., and finally, the methodology used is Scrum because the working structure meets the needs of the development team as both the end customer. In conclusion, the result is an application that helps the user to identify the location of dependences quickly and in a novel way displaying news in real time within reach your hands by means of the mobile device.